Posted by **Tony** on Friday, March 16, 2007 at 8:45pm.

Rewrite the equation as a function

-3x+4y=11

If you want to consider y as a function of x, then

y = (1/4)(3x +11)

One can also write x as a function of y.

x = (1/3)(4y - 11)

Thursday

March 23, 2017
Posted by **Tony** on Friday, March 16, 2007 at 8:45pm.

Rewrite the equation as a function

-3x+4y=11

If you want to consider y as a function of x, then

y = (1/4)(3x +11)

One can also write x as a function of y.

x = (1/3)(4y - 11)

Search